Mining technology in the artisanal extraction of gold - Romero Baylón, Alfonso (2014)
The study measures the level of influence of technology in the extraction of gold minerals by the artisanal sector, establishing the levels of use of the technology in the mining cycle in artisanal mining, which includes the main activities of extraction of gold ore. The influence of mining technology, both in the mining cycle and in the gold ore recovery cycle, would allow artisanal activity to be carried out with minimal criteria for the use of engineering and technology, the contribution of which will be to reduce the impact negative to the physical environment. Peru faces a very serious contamination problem to the physical environment caused by artisanal mining and, in its effort to remedy and curb this problem, it has issued various legal regulations such as Law No. 27651 - Law of Formalization and Promotion of Small Mining and Artisanal Mining, which was created within the appropriate legal framework for the official recognition of artisanal mining in the formal economy sector. Likewise, Law No. 27446-Law of the National System of Environmental Impact was taken as a reference. Both laws indicate that the requirements that, from the point of view of the environment, for small miners and artisanal miners will only be enforceable the Declaration of Environmental Impact and Semi-detailed Environmental Impact Studies, signed by a competent professional. For these standards to become a reality, it is necessary that mining technology in the artisanal sector cause a real impact and influence of 80%.